Identification and Functional Analysis of the Pheromone Response Factor Gene of Sporisorium scitamineum - Zhu, Guining; Deng, Yizhen; Cai, Enping; Yan, Meixin; Cui, Guobing; Wang, Zhiqiang; Zou, Chengwu; Zhang, Bin; Xi, Pinggen; Chang, Changqing; Chen, Baoshan; Jiang, Zide (Frontiers in Microbiology, 2019)
The sugarcane smut fungus Sporisorium scitamineum is bipolar and produces sporidia of two different mating types. During infection, haploid cells of opposite mating types can fuse to form dikaryotic hyphae that can colonize plant tissue. Mating and filamentation are therefore essential for S. scitamineum pathogenesis. In this study, we obtained one T-DNA insertion mutant disrupted in the gene encoding the pheromone response factor (Prf1), hereinafter named SsPRF1, of S. scitamineum, via Agrobacterium tumefaciens-mediated transformation (ATMT) mutagenesis. Targeted deletion of SsPRF1 resulted in mutants with phenotypes similar to the T-DNA insertion mutant, including failure to mate with a compatible wild-type partner strain and being non-pathogenic on its host sugarcane. qRT-PCR analyses showed that SsPRF1 was essential for the transcription of pheromone-responsive mating type genes of the a1 locus. These results show that SsPRF1 is involved in mating and pathogenicity and plays a key role in pheromone signaling and filamentous growth in S. scitamineum.